2021
DOI: 10.1021/acs.est.1c04641
|View full text |Cite
|
Sign up to set email alerts
|

Biological Mitigation of Antibiotic Resistance Gene Dissemination by Antioxidant-Producing Microorganisms in Activated Sludge Systems

Abstract: Antibiotic resistance is the principal mechanism of an evergrowing bacterial threat. Antibiotic residues in the environment are a major contributor to the spread of antibiotic resistance genes (ARGs). Subinhibitory concentrations of antibiotics cause bacteria to produce reactive oxygen species (ROS), which can lead to mutagenesis and horizontal gene transfer (HGT) of ARGs; however, little is known about the mitigation of ARG dissemination through ROS removal by antioxidants. In this study, we examine how antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…Therefore, the mitigation and treatment of antimicrobial resistance and antimicrobial contamination from the perspective of removing ARGs and antimicrobials may be a more effective strategy. Constructed wetlands (CW), advanced oxidation processes (AOP), membrane processes, and microbial fuel cells (MFC) have been reported as promising elimination methods for pollutants [ 122 , 160 , 161 , 162 , 163 ]. In the following, we summarize the existing, relatively efficient and promising antimicrobial and ARGs elimination methods.…”
Section: Methods To Mitigate Antimicrobial Contamination and Antimicr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the mitigation and treatment of antimicrobial resistance and antimicrobial contamination from the perspective of removing ARGs and antimicrobials may be a more effective strategy. Constructed wetlands (CW), advanced oxidation processes (AOP), membrane processes, and microbial fuel cells (MFC) have been reported as promising elimination methods for pollutants [ 122 , 160 , 161 , 162 , 163 ]. In the following, we summarize the existing, relatively efficient and promising antimicrobial and ARGs elimination methods.…”
Section: Methods To Mitigate Antimicrobial Contamination and Antimicr...mentioning
confidence: 99%
“…In polluted water sources, ARGs abundance showed a relatively strong correlation with the concentration of heavy metals [ 121 ]. Reactive oxygen species are thought to be the inducement of ARGs transfer, but not the only one [ 122 ]. The presence of heavy metal ions can cause oxidative stress in bacteria, and then increase intracellular reactive oxygen species levels, which may serve as a potential mechanism of heavy metals promoting the formation of ARB [ 123 ].…”
Section: The Fate Of Antimicrobial Resistance In the Environmentmentioning
confidence: 99%
“…In our previous study, we demonstrated that the nucleaseproducing Deinococcus could mitigate transformation of extracellular ARGs to Enterococcus faecalis by degrading eDNA. 18,19 Therefore, this study mainly demonstrates whether these nuclease-producing bacteria can reduce the risk of ARG dissemination in mixed bacteria sewage systems. In this study, a microbiome capable of degrading eDNA was constructed and operated by using Deinococcus radiodurans as the base microorganism.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bacteria belonging to the Deinococcus , Myxococcus , Streptomyces , Flectobacillus , Exiguobacterium , and Sphingomonas genera are known to defend against oxidative stress by producing reducing substances such as carotenoids, exopolysaccharides, and small-molecule antioxidants that efficiently scavenge ROS . We previously showed that antioxidant-producing bacteria can scavenge excess ROS (induced by antibiotics) in activated sludge, although the underlying mechanisms and genetic basis were not discerned. In addition, many bacteria are separately capable of synthesizing extracellular nucleases that degrade eDNA .…”
Section: Introductionmentioning
confidence: 99%